Temperature Field and Residual Stress of Butt Welding for IN182 Plate - Vemanaboina, Harinadh; Janardhana Raju, G.; Sreenivas, Bura (International Journal of Engineering and Technology, 2018)
The welding process is a nonlinear phenomenon in nature which leads to deformation and residual stresses in weldments. To overcome the structural changes in the weldments the computational packages can be effectively used for analyzing the changes in its life. Inconel superalloys have excellent mechanical properties and are used in the industrial applications. The present simulation is carried out for single pass butt-joint. Simulation studies are used for effective selection of process parameters for improving mechanical properties in the weld structures. In this work, coupled thermo-mechanical simulation process was carried out for predicting the temperatures, distortion and residual stress distribution in the weldments using Finite element analysis at the transverse direction on the welded surface.Â Â